Thermodynamics and kinetics of the dehydration reaction of FePO4·2H2O - Boonchom, Banjong; Puttawong, Spote (My University, 2010)
The thermal decomposition kinetics of FePO4·2H2O in dynamical air atmosphere was studied by mean TG-DTG-DTA. The stage and product of the thermal decomposition were determined. A number of kinetic models and calculation procedures were used to determine the kinetic triplet and thermodynamic parameters characterizing the dehydration process. The obtained activation energy and most kinetic model indicate the single kinetic mechanism and three-dimension diffusion as "Ginstling-Brounstein equation (D4 model)", respectively. The thermodynamic functions (ΔH*, ΔG* and ΔS*) of the dehydration reaction are calculated by the activated complex theory and indicate that the process is non-spontaneous without connecting with the introduction of heat. The kinetic and thermodynamic results were satisfactory which present good correlation with a linear correlation coefficient close to unit a low standard deviation. © 2010 Elsevier B.V. All rights reserved.
Keywords: Inorganic compounds; Non-isothermal kinetics; Thermodynamic properties; Thermogravimetric analysis (TGA)